Biochemical characterisation of a cassava (Manihot esculenta Crantz) diversity panel for post-harvest physiological deterioration: Metabolite involvement and environmental influence - Drapal, Margit; Ovalle Rivera, Tatiana M; Luna Melendez, Jorge Luis; Perez-Fons, Laura; Tran, Thierry; Dufour, Dominique; Becerra Lopez Lavalle, Luis Augusto; Fraser, Paul D. (Elsevier, 2024)
Cassava (Manihot esculenta Crantz) produces edible roots, a major carbohydrate source feeding more than 800 million people in Africa, Latin America, Oceania and Asia. Post-harvest physiological deterioration (PPD) renders harvested cassava roots unpalatable and unmarketable. Decades of research on PPD have elucidated several genetic, enzymatic and metabolic processes involved. Breeding populations were established to enable verification of robust biomarkers for PPD resistance. For comparison, these PPD populations have been cultivated concurrently with diversity population for carotenoid (β-carotene) content. Results highlighted a significant variation of the chemotypes due to environmental factors. Less than 3% of the detected molecular features showed consistent trends between the two harvest years and were putatively identified as phenylpropanoid derived compounds (e.g. caffeoyl rutinoside). The data corroborated that ∼20μg β-carotene/g DW can reduced the PPD response of the cassava roots to a score of ∼1. Correlation analysis showed a significant correlation of β-carotene content at harvest to PPD response (R2 -0.55). However, the decrease of β-carotene over storage was not significantly correlated to initial content or PPD response. Volatile analysis observed changes of apocarotenoids derived from β-carotene, lipid oxidation products (alkanes, alcohols and carbonyls and esters) and terpenes. The majority of these volatiles (>90%) showed no significant correlation to β-carotene or PPD. Observed data indicated an increase (∼2-fold) of alkanes in varieties with β-carotene >10μg/g DW and a decrease (∼60%) in varieties with less β-carotene. Fatty acid methyl esters with a chain length >C9 were detected solely after storage and show lower levels in varieties with higher β-carotene content. In combination with correlation values to PPD (R2 ∼0.3; P-value >0.05), the data indicated a more efficient ROS quenching mechanism in PPD resistant varieties.